KEMAMPUAN MENULIS PUISI BEBAS SISWA KELAS V SD NEGERI LAMREUNG ACEH BESAR - Said Darnius (Universitas Syiah Kuala, 2022)
The study is titled “The Ability to Write Poetry Free of Grade V Students of Elementary Schools Negeri Lamreung Aceh Besar”. The problem formulation of this study is “How the Ability to Write Poetry Free of Grade V Students of Elementary Schools Negeri Lamreung Aceh Besar?”. This study aims to determine The Ability to Write Poetry Free of Grade V Students of Elementary Schools Negeri Lamreung Aceh Besar. The hypothesis of this study is the Ability to Write Poetry Free of Grade V Students of Elementary Schools Negeri Lamreung Aceh Besar still not enough. The approach used in this approach is quantitative. The type of research is descriptive statistics that serves to describe or give an idea of the object under study through sample data or population as is, without doing analysis and make conclusions that apply to the public. The sample of this study is Grade V Students of Elementary Schools Negeri Lamreung Aceh Besar which amounted to 21 students. Data collection techniques used in this study is a test. From the data obtained, it is known that the ability of grade V students in writing poetry to reach less category with an average value of 51,381 (topography); 11,429 (diction); 11,751 (images); 9,762 (concrete words); 9,476 (style of language); and 4,905 (rhyme). Based on student learning outcomes proves that the hypothesis of this study which states that the ability to write poetry is free of grade V students of Elementary Schools Negeri Lamreung Aceh Besar acceptable.